INTERVENTION OF STATE SOVEREIGNTY THROUGH RELEASING STATE SECRECY BY WIKILEAKS - Engla Puspita Haria (LP3M STIH Painan, 2019)
The increasing number of disclosure of state secrecy in this age create by Wikileaks make the impact for state sovereignty such as stability of state, disturb the relationship between the state, dysfunction of government and political and economic instance. This number happened because of some factors:1) insufficiency of sophisticated technological support provided by related state, advancement and introducing new technology, collision between staff members. corruptions, and international criminal syndicated:2)the inconstancy law regulated the criminal act about secrecy state;3)technological advances while the human resources that are not reliable. But in other hand, people have right to know and it remarkable in Declaration of Human Right article 19 But there is no regulation at national and international level for Wikileaks. In this research, the study will investigate two problems: 1) what the impact for state sovereignty because of disclosure st ate secrecy; and 2) what is the legal action to protect state secrecy and study will find the problem of this research and create some offered solution and use the ultimate value in of all part the research with use the existence of legal theory, legal pra ctice, norm or regulations, legal fact and indicated the conflict either. So this research will use normative type of research. In fact, in this research, study has analyze the case of Wikileaks and found that wikileaks already disclosure the data that ver y important for state sovereignty. Most of their documents are from the people who steal from diplomatic cable of state. This act teaches the people to not appreciate with state secrecy which has related with state sovereignty So, from this fact study has some conclusion that for some documents, they already do state secrecy intervention and should be banned for this site and gives punishment as international law or national law and at national level they should raise the protection their state secrecy by c reate new regulation